2015
DOI: 10.2220/biomedres.36.371
|View full text |Cite
|
Sign up to set email alerts
|

<b>Upregulation of energy metabolism-related, p53-target TIGAR and SCO2 in HuH-7 cells with p53 mutation by geranylgeranoic acid tr</b><b>eatment </b>

Abstract: Metabolic alternation in cancer cells is one of the most common characteristics that distinguish malignant cells from normal cells. Many studies have explained the Warburg hypothesis that cancer cells obtain more energy from aerobic glycolysis than mitochondrial respiration. Here, we show that a branched-chain C-20 polyunsaturated fatty acid, geranylgeranoic acid (GGA), induces upregulation of the cellular protein levels of TP53-induced glycolysis and apoptosis regulator (TIGAR) and synthesis of cytochrome c o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…A deregulation in any of the main glucose metabolic processes (glycolysis, TCA cycle, or gluconeogenesis) results in dysfunction in the electron transport chain that in turn affects ATP production to mitochondrial membrane potential breakdown signifying the drop in the pool of active mitochondria. Though TIGAR and SCO2 are well involved in regulating glycolysis and oxidative phosphorylation pathways, respectively, the literature suggests they are well documented in mitochondrial respiration as well 67,69‐73 . In the present study, we found that the absence of TCF19 or p53 triggers the deregulation of TIGAR and SCO2 which causes aberrant cellular glucose homeostasis and consequently impaired mitochondrial respiration.…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…A deregulation in any of the main glucose metabolic processes (glycolysis, TCA cycle, or gluconeogenesis) results in dysfunction in the electron transport chain that in turn affects ATP production to mitochondrial membrane potential breakdown signifying the drop in the pool of active mitochondria. Though TIGAR and SCO2 are well involved in regulating glycolysis and oxidative phosphorylation pathways, respectively, the literature suggests they are well documented in mitochondrial respiration as well 67,69‐73 . In the present study, we found that the absence of TCF19 or p53 triggers the deregulation of TIGAR and SCO2 which causes aberrant cellular glucose homeostasis and consequently impaired mitochondrial respiration.…”
Section: Discussionmentioning
confidence: 43%
“…The involvement of SCO2 and TIGAR in mitochondrial respiration has been established in the context of metabolic stress adaptation in various cancers, including HCC. 61,[65][66][67][68][69][70][71][72][73] As these genes now were known to be regulated by TCF19/p53 complex, next in order to understand their co-regulatory function in metabolic processes, we measured lactate production, ECAR, OCR, and ATP production. We found that the lactate production increases in case of TCF19 as well as p53 knocked down stable HepG2 cells (Figure 7A) indicating dysfunctional TIGAR leads to higher rate of glycolysis.…”
Section: Regulation Of Cellular Bioenergetics By Tcf19 and P53 Indicates Their Involvement In Similar Pathwaysmentioning
confidence: 99%
“…The cell death is finally detectable 6-8 h after adding GGA (19). Recently, we reported that GGA at micromolar concentrations upregulated the cellular protein levels of TP53-induced glycolysis and apoptosis regulator (TIGAR) and synthesis of cytochrome c oxidase 2 (SCO2) without their transcriptional upregulation and consequently induced a metabolic shift from aerobic glycolysis to mitochondrial respiration, as revealed by metabolomics analysis in 2 h (20). In guinea pig fibroblast-derived cell lines, GGA induced a transient increase of mitochondrial superoxide production in 15 min and dissipation of m in 2 h, and cell death became evident in 6 h (21).…”
mentioning
confidence: 98%
“…Iwao et al used UHPLC/TOF-MS-based metabolomics to study the underlying mechanism of its anti-HCC effect. 84 Their results showed that GGA could increase fructose 6-phosphate and spermine while decreasing fructose 1,6-diphosphate and spermidine, suggesting that GGA may shift Huh7 cells from aerobic glycolysis to mitochondrial respiration via upregulating TIGAR and SCO2 protein levels. Dehydroepiandrosterone (DHEA), a steroid secreted by the brain, gastrointestinal tract, adrenal cortex and gonads, is reported to have antiproliferative properties.…”
Section: Metabolomics In Treatment Evaluationmentioning
confidence: 97%